2020
DOI: 10.1111/scs.12821
|View full text |Cite
|
Sign up to set email alerts
|

‘Living Together With Dementia’: preliminary results of a training programme for family caregivers

Abstract: Living Together With Dementia': preliminary results of a training programme for family caregivers The aim of this article was to present the preliminary results of a training programme for family caregivers of people with dementia at an early to moderate stage living at home-'Living Together With Dementia'. In this randomised controlled trial, 27 family caregivers who met the inclusion criteria were recruited from the neurology outpatient consultation clinic of a hospital in the north of Portugal and randomise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
4
9
0
1
Order By: Relevance
“…Concerning the profile of dependent older persons involved in the present study, a majority were women with an average age of 79 years, and in most cases (40%) were diagnosed with dementia. This is in line with the Organization for Economic Cooperation and Development (2019) report, as well as other national and international studies, which found women to be the main caregivers (Sousa et al, 2020a;Ara ujo et al, 2018;Pego and Nunes, 2018) and dementia as a more prevalent illness of older persons (Livingston et al, 2020;Sousa et al, 2020b;Pego and Nunes, 2018;Musich et al, 2017). Concerning older adults, in isolation and those with cognitive decline/dementia, the WHO alerts about the likelihood of increased anxiety, anger, stress, restlessness and withdrawn during the outbreak or while To what extent have the restrictions imposed by the Coronavirus pandemic changed your routines as a caregiver?…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Concerning the profile of dependent older persons involved in the present study, a majority were women with an average age of 79 years, and in most cases (40%) were diagnosed with dementia. This is in line with the Organization for Economic Cooperation and Development (2019) report, as well as other national and international studies, which found women to be the main caregivers (Sousa et al, 2020a;Ara ujo et al, 2018;Pego and Nunes, 2018) and dementia as a more prevalent illness of older persons (Livingston et al, 2020;Sousa et al, 2020b;Pego and Nunes, 2018;Musich et al, 2017). Concerning older adults, in isolation and those with cognitive decline/dementia, the WHO alerts about the likelihood of increased anxiety, anger, stress, restlessness and withdrawn during the outbreak or while To what extent have the restrictions imposed by the Coronavirus pandemic changed your routines as a caregiver?…”
Section: Discussionsupporting
confidence: 91%
“…The main results of this study show that the family caregivers participants were mostly women aged over 50 years, in the working age and devoting more than 8 h per day to care. These results corroborate well-known current evidence about this topic (Sousa et al , 2020a, 2020b; Araújo et al , 2018), as well as with a more recent report from the Organization for Economic Co-operation and Development (Organization for Economic Co-operation and Development, 2019), in which Portugal has the greatest gender imbalance, with over 70% of informal carers being women. The report also shows that concerning the average number of hours devoted to care by caregivers, there was a significant increase of about 6% during the pandemic outbreak, considering a statistically significant value (Organization for Economic Cooperation and Development, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Cuidadores em coabitação prestam geralmente cuidados de forma intensa e prolongada, sendo a oportunidade de descanso menor, quando comparados com cuidadores que não coabitam com o recetor de cuidados ou com cuidadores formais. (5) "O cuidado continuado impõe uma condição física, emocional, social e encargo económico para os cuidadores e família," (6) existindo relação significativa entre a sobrecarga percebida pelo cuidador e as caraterísticas sociodemográficas, clínicas e as necessidades de cuidados a prestar. (7) O efeito da prestação de cuidados não se restringe ao cuidador familiar (CF).…”
Section: Introductionunclassified
“…The entire programme was built and validated within a conceptual framework using a focus group, integrative literature review, and a Delphi study (Sousa et al, 2018(Sousa et al, , 2016a(Sousa et al, , 2016b. A randomised controlled trial protocol was developed to address its experimental validation, after which a short-term efficacy study took place (Sousa et al, 2020).…”
mentioning
confidence: 99%